Suicidal behavior among inpatients with severe mental conditions in a public mental health hospital in Uganda - Abaatyo, Joan; Favina, Alain; Bulega, Steven Elijah; Kaggwa, Mark Mohan (BMC psychiatry, 2023)
Background: Suicidal behaviors are prevalent among inpatients with severe mental conditions and may result in many dying by suicide. Few studies have focused on the burden of suicidal behaviors among these inpatients in low-income settings, despite suicide being consistently higher in lower-income countries such as Uganda. This study, therefore, provides the prevalence and associated factors of suicidal behaviors and suicide attempts among inpatients with severe mental conditions in Uganda. Methods: This was a retrospective chart review of all individuals admitted with severe mental conditions to a large psychiatry inpatient unit in Uganda for four years (2018–2021). Two separate logistic regressions were conducted to determine the factors associated with suicidal behaviors or suicidal attempts among the admitted individuals. Results: The prevalence of suicidal behavior and suicidal attempts among 3104 (mean age = 33, Standard deviation [SD] = 14.0; 56% were males) were 6.12% and 3.45%, respectively. Having a diagnosis of depression increased the likelihood of both suicidal behaviors (adjusted odds ratio [aOR]: 5.36; 95% confidence interval [CI]: 2.14–13.37; p =0.001) and attempts (aOR: 10.73; 95% CI: 3.44–33.50; p < 0.001). However, a diagnosis of substance-related disorder increased the likelihood of having attempted suicide (aOR: 4.14; 95% CI: 1.21–14.15; p = 0.023). The likelihood of having suicidal behavior decreased as one increased in age (aOR: 0.97; 95% CI: 0.94–0.99; p = 0.006) and increased among individuals reporting stress from financial constraints (aOR: 2.26; 95% CI: 1.05–4.86; p = 0.036). Conclusion: Suicidal behaviors are common among inpatients managed for severe mental health conditions in Uganda, especially those with substance use and depressive disorders. In addition, financial stressors are a main predictor in this low-income country. Therefore, regular screening for suicide behaviors is warranted, especially among individuals with depression, and substance use, among those who are young, and among those reporting financial Aconstraints/stress.
Keywords: Suicidal behaviors; Suicidal attempt; Suicide; Financial constraints; Depression; Substance use; Severe mental conditions; Uganda